2022
DOI: 10.1002/cpp.2753
|View full text |Cite
|
Sign up to set email alerts
|

Potentially traumatic events and post‐traumatic growth among Chinese peacekeepers: A moderated mediation model

Abstract: Peacekeepers are inherently exposed to potentially traumatic events (PTEs) in the line of duty. However, little is known about whether PTEs during peacekeeping missions may foster post‐traumatic growth (PTG) among peacekeepers and its mechanisms. This study aimed to investigate the association between PTEs and PTG among Chinese peacekeepers, as well as the mediating role of coping style and the moderating role of resilience. Five hundred ninety‐five Chinese peacekeepers completing the United Nations (UN) peace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Totally 9 articles reported on behavioral lifestyle factors as health risk factors of UN peacekeepers in multiple troop-contributing and host countries [ 14 , 30 , 52 , 71 , 93 , 104 , 114 , 125 , 131 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Totally 9 articles reported on behavioral lifestyle factors as health risk factors of UN peacekeepers in multiple troop-contributing and host countries [ 14 , 30 , 52 , 71 , 93 , 104 , 114 , 125 , 131 ].…”
Section: Resultsmentioning
confidence: 99%
“…One study explored severity PTSD symptoms impacted by exposure to combat directly and indirectly through fear and sexual harassment among U.S. peacekeepers in Somalia [ 130 ]. One study explored understanding the complex association among peacekeepers’ PTSD, coping style, and resilience by focusing on the experiences of Chinese peacekeepers in South Sudan [ 131 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have suggested the expression of positive emotion words and negative emotion words can improve an individual’s mental state, but the effectiveness of positive emotions produces more ( Burton and King, 2004 ; Pennebaker and Chung, 2007 ). The expression of positive experiences shows that patients are experiencing deliberate rumination, which is more likely to facilitate posttraumatic growth ( Qu et al, 2022 ). Thus, the expression of positive emotion is more associated with the amount of mood change.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the impact of war on psychological resilience indicate the negative effects of distress, anxiety, and uncertainty on individual and social resilience [e.g., (2)(3)(4)]. Other studies indicate that in face of stressful conditions (e.g., COVID-19 and armed conflict) resilience is predicted not only by negative effects (such as perceived threats) but also by positive effects (such as hope) (5,6).…”
Section: Introductionmentioning
confidence: 99%